A laboratory investigation of cutting damage to the steel-concrete interface. (December 2020) - Zhang, Zhidong; Shakoorioskooie, Mahdieh; Griffa, Michele; Lura, Pietro; Angst, Ueli
Abstract: The microstructure of the steel-concrete interface (SCI) in reinforced concrete is closely related to corrosion of reinforcing steel bars. Accordingly, characterization of the SCI is receiving increasing research attention. For microscopical observations of the SCI, a cutting process is needed to create a flat cross-section. Cutting carries the risk of damaging the SCI because of the considerable difference of hardness between concrete and steel. However, studies on characterizing the microstructure of the SCI rarely consider the damage induced by the potentially inappropriate cutting process. This study investigated the damage created by three cutting methods, namely, mechanical sawing, laser cutting, and combined laser-water cutting by the Laser MicroJet technology (LMJ). The SCI of the cut sections was imaged by scanning electron microscopy equipped with a backscattered electron detector. Additionally, the specimens were non-invasively studied by X-ray microtomography before and after cutting, to compare the impact of various cutting techniques on inducing damage to the SCI beneath the cutting surface. The results showed that if a bleed water zone (BWZ) is present, the cutting technique and protocol can significantly influence the morphology of this zone and adjacent regions. This study recommends an optimized mechanical sawing protocol with low feed speed as this led to considerably less SCI damage than laser and LMJ cutting. Moreover, it was found that adjusting the cutting direction can further significantly reduce the damage created during cutting. The least damage was found when the saw blade cut through the steel before cutting the BWZ. The main problem with laser cutting was heat generated even for a relatively low laser power; therefore, a heat-affected zone was created which significantly altered the microstructural features of the SCI not only on the cutting surface but also a certain depth below the surface. In LMJ cutting, this thermal effect was significantly reduced, however, the high-pressure water eroded the porous SCI and caused cracks. These effects can penetrate along the BWZ into the interior material. To complete this study, two applications demonstrate that the optimized mechanical sawing protocol is applicable to concrete specimens with rebars of actual size and corroded rebars.